Effect of the BaO addition on properties of alkali borosilicate glasses from sub-bituminous fly ash. (2018) - Rachniyom, W.; Wiwatkanjana, P.; Ruangtaweep, Y.; Kaewkhao, J.
Abstract: Alkali borosilicate glasses were prepared by using sub-bituminous fly ash (SFA) and B2 O3 as raw material, Na2 O as fluxing agent. The effects of BaO addition were investigated in formula x BaO: (65-x) B2 O3 : 20 Na2 O: 15 SFA (where x = 5, 10, 15, 20 and 25 wt%.) and melted at 1, 200 °C by melt quenched technique. All glass samples were analyzed then compared their properties of density, refractive index, hardness, absorption spectra and radiation shielding properties. The results were showed better properties with increasing of BaO content. The density, refractive index and hardness values of glass samples were increased with increasing of BaO content and showed highest value at 2.857 g/cm 3, 1.5567 and 494.867 HV, respectively. The result of absorption spectra found the ferric and ferrous ions peaks occurred at 440 nm and 1, 050 nm. The color of glass samples caused by ferric ions which obtianed from SFA. However, the color of glasses with higher BaO were showed more light green and brightness. The half value layer (HVL) of glass found to be decreased with higher BaO concentration, due to higher gamma ray absorption cross section of Ba in glass matrices. The glass containing 25 wt%. of BaO is the best shielding glass in this experiment and better than serpentite-hematite concrete.